Robustness design of templates for logic OR operation CNN in gray-scale images - Qun ZHANG; Le-quan MIN (Tongxin xuebao)
A kind of gray-scale logic OR operation (GLOGOR) CNN was proposed by formulating the logic OR algo-rithms for gray-scale images. It could perform a pixel-wise logic OR operation on corresponding elements of two gray-scale images. A theorem was established to design the robustness template parameters of GLOGOR CNN, and a ri-gorous mathematical proof was given. The theorem provided parameter inequalities for determining parameter intervals to implement the corresponding tasks. The simulation results illustrate the effectiveness of the methodology.